Risk-reducing strategies for women carrying brca1/2 mutations with a focus on prophylactic surgery - Mokbel Kefah; Bismohun Selina; Salhab Mohamed (BMC, 2010)
Abstract Background Women who have inherited mutations in the BRCA1 or BRCA2 genes have substantially elevated risks of breast and ovarian cancer. Mutation carriers have various options, including extensive and regular surveillance, chemoprevention and risk-reducing surgery. The aim of this review is to provide an up-to-date analysis and to subsequently summarise the available literature in relation to risk-reducing strategies, with a keen focus on prophylactic surgery. Methods The literature review is facilitated by Medline and PubMed databases. The cross-referencing of the obtained articles was used to identify other relevant studies. Results Prophylactic surgery (bilateral mastectomy, bilateral salpingo-oophorectomy or a combination of both procedures) has proved to be the most effective risk-reducing strategy. There are no randomised controlled trials able to demonstrate the potential benefits or harms of prophylactic surgery; therefore, the evidence has been derived from retrospective and short follow-up prospective studies, in addition to hypothetical mathematical models. Based on the current knowledge, it is reasonable to recommend prophylactic oophorectomy for BRCA1 or BRCA2 mutation carriers when childbearing is completed in order to reduce the risk of developing breast and ovarian cancer. In addition, women should be offered the options of rigorous breast surveillance, chemoprevention with anti-oestrogens--especially for carriers of BRCA2--or bilateral prophylactic mastectomy. Conclusion The selection of the most appropriate risk-reducing strategy is not a straightforward task. The impact of risk-reducing strategies on cancer risk, survival, and overall quality of life are the key criteria considered for decision-making. Notably, various other factors should be taken into consideration when evaluating individual mutation carriers' individual circumstances, namely woman's age, morbidity, type of mutation, and individual preferences and expectations. Although prospective randomised controlled trials concerned with examining the various interventions in relation to the woman's age and type of mutation are needed, randomisation is extremely difficult and rather deemed unethical given the current available evidence from retrospective studies.